2016
DOI: 10.1002/gps.4540
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral variant frontotemporal dementia: advanced disease stages and death. A step to palliative care

Abstract: Advanced bvFTD is characterized by severe cognitive impairment and physical disabilities. BvFTD leads to a premature death. Our findings stress the importance of strategies that maximize patient comfort in advanced disease stages and allow for a peaceful death. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…The high frequency of acute myocardial infarction in FTLD found here differs from that of previous studies, where pneumonia was the leading cause of death [3]. FTLD is associated with cardiovascular comorbidities and patients are predisposed for respiratory diseases [25,26].…”
Section: Discussioncontrasting
confidence: 87%
“…The high frequency of acute myocardial infarction in FTLD found here differs from that of previous studies, where pneumonia was the leading cause of death [3]. FTLD is associated with cardiovascular comorbidities and patients are predisposed for respiratory diseases [25,26].…”
Section: Discussioncontrasting
confidence: 87%
“…Our result indicating admission to residential care 2.8 years after diagnosis aligns with a recent German study that reported a median of 2.0 ± 2.5 years between diagnosis and residential care admission for a bvFTD cohort. 31 Future studies should investigate time from diagnosis to residential care admission in a larger cohort of bvFTD phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…(19) We also found five reports of caregivers mentioning distress regarding caring for someone with FTD or coping with life after FTD. Diehl-Schmid and colleagues (28) report that "patients with bvFTD are less likely to be cared for at home until death than patients with Late Onset Dementia (LOD). BvFTD caregivers are often faced with the double burden of providing care while performing other roles, such as parenting, working, and managing the household."…”
Section: Discussion Of Burdens In Healthcare Access and Caregiver Dis...mentioning
confidence: 99%
“…In the vast majority of patients, the course of bvFTD is characterized by a progressive disability. Patients lose the ability of self-care, most patients become unable to carry out even the basal activities of daily living and ultimately become dependent on long-term care (28). Recommendations Specifically, when older adults start displaying behaviours that are criminal and a change from their baseline behaviour, an evaluation for neurologic disorders and possibly neuropsychological testing, coupled with neuroimaging, is helpful in ruling out a neurodegenerative disease.…”
Section: Capacity or Autonomymentioning
confidence: 99%